KNOWLEDGE OF PREGNANT WOMEN IN THE THIRD TRIMESTER ABOUT CONGENITAL DEAFNESS AND FREQUENCY OF ANTENATAL CARE DURING THE COVID-19 PANDEMIC - Nicha Karmila Tamtiana, ,- (2021)
Background: In Indonesia, the prevalence of hearing loss in 4.2% and the prevalence of congenital deafness is 0.1%. WHO estimates that about 60% of hearing loss in caused by causes that can be prevented through improved maternal and child health practice from routine ANC visits and screening for pregnancy complications. During the COVID-19 pandemic, pregnant women are afraid to do a pregnancy check, the frequency of ANC is irregular which will affect the health of the fetus in the womb. Methods: The research method is observational analysis with a cross-sectional approach. The sample size is 110 pregnant women in the third trimester with phsysiological pregnancies and willing to be respondents. The sampling technique was purposive sampling. Data were analyzed using a chi-square statistical test. Result: The result of the analysis showed that 49.1% of mothers had good knowledge of congenital deafness, 28.25% had poor knowledge, and 22.7% had sufficient knowledge. As many as 76.4% of mothers made ANC visits not according to standars and only 26 (23.6%) mothers made ANC visits according to standard. The result of the statistical analysis test it has been shown that there is an association between knowledge of pregnant women in the third trimester about congenital deafness with the frequency of antenatal care during the COVID-19 pandemic with p-value = 0.029 (p<0.05). Conclusion: There is a link between the knowledge of pregnant women in the third trimester about congenital deafness with the frequency of antenatal care during the COVID-19 pandemic. The COVID-19 pandemic has prevented pregnant women from carrying out ANC in health service and increased the anxiety of pregnant women.